Analysis of the colombian scientific production in chemistry. Wokdatabase(2001-2012) - Nubia Yaneth Gómez Velasco; Ana Emilce Jiménez González; Sara Cristina Guerrero; Yolima Ayala Sánchez (Logos Ciencia & Tecnología, 2014)
An exploratory analysis is presented through somes cientometric indicators of production of articles in thearea of chemistry with Colombian author institutional affiliation,reported in the Web of Knowledge(2001 - 2012). Indicators analyzed: Number of citations, articles peryear, number of authors per article. The study was complemented with bivariat estatistical tests and techniques. Among the results published numerous articles found reference three to five authors,with predominant from 2009 to the United States and Spain, grouped into areasof knowledge and Biochemistry&Molecular Biology Biophysics.